Brand Loyalty dan Pengaruhnya terhadap Keputusan Pembelian - Marisi Butarbutar; Efendi Efendi; Sudung Simatupang (Universitas Winaya Mukti, 2021)
One of the famous culinary industry brands in Pematangsiantar City is Toko Roti Ganda. The famous brand Of Toko Roti Ganda makes many visitors who have an impact on traffic jams. The phenomenon is due to the famous Toko Roti Ganda in the community makes the brand a top priority of the community compared to other brands for visitors who come. This study aims to determine the effect of brand loyalty on purchasing decisions at Toko Roti Ganda. This research was conducted on all residents of Pematangsiantar City and Simalungun Regency who have ever made purchases at the Roti Ganda. Furthermore, the results of respondents obtained from the study were 123 respondents. The research method was carried out by qualitative and quantitative. The results show that the research criteria are declared valid and reliable with the indicators met. For normality results that all research variables are normally distributed, the coefficient of determination shows that brand loyalty can explain purchasing decisions by fifty-four percent. At the same time, the rest is influenced by other factors not discussed in the study. Then the regression equation test shows a positive effect of brand loyalty on purchasing decisions and accepts the hypothesis that brand loyalty affects purchasing decisions. It means that brand loyalty for consumers greatly influences them in making purchase decisions, and brand loyalty can be a factor that can make consumers make decisions about purchases.